Measure The Level of English Comprehension for First Semester Students - Afifah, Naeli Lailatul; Anggraeni, Syahyuni Anggun (Universitas Djuanda, 2024)
It is very important to form soft skills, this study is to determine the level of English proficiency of the PGSD Semester 1 study program on the campus Djuanda University is one of the universities located on Jagorawi Toll Road No. 1, Ciawi, Ciawi District, Bogor Regency, West Java 16720, which of course has different English language skills. With this research, it is hoped that you will know the level of understanding of English discussion of the PGSD Semester 1 study program at the University of Djuanda campus. The method used is a qualitative method using the interview method, so that with this method a clear picture of the level of English understanding of PGSD Semester 1 students will be known. The findings are the most important part of the abstract and should not exclude their range and quality; Therefore, the results of this study show that there are some students who still have difficulty in speaking English, but experience better improvement than when they were high school students. In English, more emphasis is placed on vocabulary mastery, if the student is used to pronouncing the wrong word, there will be a tendency for him not to be able to provide clear information, the more vocabulary mastered by the student, the easier it is to learn English.In the context of this study, certain assessment methods such as written tests proved to be more effective in measuring the level of English comprehension than oral tests but, This conclusion also highlights the need for a holistic approach that considers different aspects of language understanding for more accurate evaluation, the implication of this assessment is the importance of using varied and comprehensive assessment methods in evaluating English comprehension being an important factor in the development of more effective educational approaches.